Roughness effects of textured surfaces in hydrodynamic lubrication - Bahi, Youssef; Gadari, Mhammed El; Rahmoune, Miloud (Zielona Góra: Uniwersytet Zielonogórski)
Several studies have been conducted to improve and model the lubricated contact between surfaces. The main subjects were defining the hydrodynamic parameters to reduce energy losses and protect the environment. Some of the proposed models have studied the effect of textures in hydrodynamic lubrication and have proved that adapted shapes and geometries can improve the performance of lubricated contacts.
Keywords: finite difference; texture; roughness; HD pressure; lifting force; friction; leakage